Echocardiographic findings associated with mortality or transplant in patients with pulmonary arterial hypertension: A systematic review and meta-analysis - Baggen, V.J.M. (Neth Heart J, 2016)
BACKGROUND: Identification of patients at risk of deterioration is essential to guide clinical management in pulmonary arterial hypertension (PAH). This study aims to provide a comprehensive overview of well-investigated echocardiographic findings that are associated with clinical deterioration in PAH. METHODS: MEDLINE and EMBASE databases were systematically searched for longitudinal studies published by April 2015 that reported associations between echocardiographic findings and mortality, transplant or clinical worsening. Meta-analysis using random effect models was performed for echocardiographic findings investigated by four or more studies. In case of statistical heterogeneity a sensitivity analysis was conducted. RESULTS: Thirty-seven papers investigating 51 echocardiographic findings were included. Meta-analysis of univariable hazard ratios (HRs) and sensitivity analysis showed that presence of pericardial effusion (pooled HR 1.70; 95 % CI 1.44–1.99), right atrial area (pooled HR 1.71; 95 % CI 1.38–2.13) and tricuspid annular plane systolic excursion (TAPSE; pooled HR 1.72; 95 % CI 1.34–2.20) were the most well-investigated and robust predictors of mortality or transplant. CONCLUSIONS: This meta-analysis substantiates the clinical yield of specific echocardiographic findings in the prognostication of PAH patients in day-to-day practice. In particular, pericardial effusion, right atrial area and TAPSE are of prognostic value. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi: 10.1007/s12471-016-0845-3) contains supplementary material, which is available to authorized users.